2019
DOI: 10.3390/mi10110772
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Leukocyte Viability and Damage in Spiral Microchannel and Contraction-Expansion Array

Abstract: Inertial separation techniques in a microfluidic system have been widely employed in the field of medical diagnosis for a long time. Despite no requirement of external forces, it requires strong hydrodynamic forces that could potentially cause cell damage or loss during the separation process. This might lead to the wrong interpretation of laboratory results since the change of structures and functional characteristics of cells due to the hydrodynamic forces that occur are not taken into account. Therefore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Cell loss and damage due to fluid shear stress is a function of both stress magnitude and exposure time. The less exposure time to a particular shear stress, the less the chances of having cells damaged [ 49 ]. The critical magnitude of shear stress in this study for a 14 µm particle which is set to represent a WBC, remains relatively below the known threshold of WBC damaging shear stress [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell loss and damage due to fluid shear stress is a function of both stress magnitude and exposure time. The less exposure time to a particular shear stress, the less the chances of having cells damaged [ 49 ]. The critical magnitude of shear stress in this study for a 14 µm particle which is set to represent a WBC, remains relatively below the known threshold of WBC damaging shear stress [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The less exposure time to a particular shear stress, the less the chances of having cells damaged [ 49 ]. The critical magnitude of shear stress in this study for a 14 µm particle which is set to represent a WBC, remains relatively below the known threshold of WBC damaging shear stress [ 49 ]. Additionally, the low exposure time of WBCs to these amounts of shear stress, which equals to the amount of time that a single cell manages to pass through the microchannel (about 0.306 s) further lessons the possibility of losing WBCs in the process.…”
Section: Resultsmentioning
confidence: 99%
“…Purvis et al showed that elongational stress induces platelet aggregation as well as impairs the platelet's response to ADP [48]. Leukocyte suspensions in contraction expansion array microchannels (dominated by shear and elongational stresses), used for inertial cell separation, showed increased intracellular damage over spiral microchannel designs (dominated only by shear stress) [49]. This suggests that the elongational stresses are the main contributing factor to the observed intracellular damage.…”
Section: Effect Of Elongational Stressmentioning
confidence: 99%
“…The use of immobile microfluidics without the external force among cell manipulation techniques has attracted great interest. Recently, microfluidic systems used are suitable for simple and highly efficient cell separation and analysis [5]. Silicone is the first choice among microfluidic system manufacturing when considering advantages such as its readiness, chemical compatibility and thermostability.…”
Section: Cell Manipulationmentioning
confidence: 99%